Strategies for the Neutralization of the Carbon Footprint at the University of the State of Mexico - Reynoso, Mariana Ortiz; Maya, Juan Roberto Calderon; Mercado, Noe Armando Colin; Garcia, Yoselin Montoya (Journal of Sustainability Perspectives, 2025)
Climate Change, driven by greenhouse gas emissions (GHG), demands concrete responses from all sectors, including the higher education party. This research aimed to calculate the carbon footprint (CF) generated by the core activities of the Autonomous University of the State of Mexico (Universidad Autónoma del Estado de México, UAEMEX) from 2021 to 2024, and to propose strategies for its neutralization. A hybrid methodology was adopted, based on international standards such as ISO 14064-1:2019, PAS 2050, PAS 2060 and the Greenhouse Gas Protocol, adapted to the characteristics of Higher Education Institutions (HEIs). This approach classified emissions into three scopes: direct emissions from fossil fuels (Scope 1), indirect emissions from electricity consumption (Scope 2) and other indirect emissions associated with waste management, paper consumption and infrastructure (Scope 3). The results indicate a 99% increase in the institutional carbon footprint between 2021 and 2022, linked to the resumption of face-to-face activities caused by COVID-19, subsequently by stabilization in the generation of HC in the subsequent years. Effective mitigation actions were identified, avoiding nearly 10 million kg CO₂e, with emphasis on sustainable university transport, process digitalization and carbon absorption through green areas. The study proposes a comprehensive neutralization plan and a replicable methodology, positioning UAEMEX as a national benchmark in university sustainability and contributing to global climate commitments through institutional management.